Nilai – Nilai Dakwah Dalam Tradisi Megengan Pada Masyarakat Jawa Di Distrik Salawati Kabupaten Sorong - Fattah, Ali Nur; kahina, Dwi iin (Al-Hikmah: Jurnal Dakwah dan Komunikasi, 2024)
This research aims to examine the cultural procession of the Megengan tradition and the da'wah values it embodies. Using qualitative methods and a phenomenological approach, the study utilizes both primary and secondary data collected through observation, interviews, and documentation. Data analysis involves reduction, presentation, and conclusion drawing. The findings indicate that the Megengan tradition in the Javanese community of Salawati District includes several key activities: grave pilgrimage to offer prayers, speeches by clerics, recitation of Surah Yasin and tahlil, and distribution of shadaqahan (food) after the event. The da'wah values identified include discipline, as the tradition is observed at the end of Sya'ban; honesty, in preparing for Ramadan; hard work, reflected in sharing food; cleanliness, essential for a comfortable event; competition in doing good during fasting; faith, as spiritual preparation for Ramadan; friendship, fostered through community interactions; sharing, through communal food distribution; and brotherhood, emphasizing care among community members.